Solid waste management in the context of the waste hierarchy and circular economy frameworks: An international critical review - Awino, Florence Barbara; Apitz, Sabine E. (Integrated environmental assessment and management, 2024)
Growing populations and consumption drive the challenges of solid waste management (SWM); globalization of transport, food production, and trade, including waste trading, distributes risks worldwide. Using waste hierarchy (WH; reduce, reuse, and recycle) and circular economy (CE) concepts, we updated a conceptual waste framework used by international organizations to evaluate SWM practices. We identified the key steps and the important factors, as well as stakeholders, which are essential features for effective SWM. Within this updated conceptual framework, we qualitatively evaluated global SWM strategies and practices, identifying opportunities, barriers, and best practices. We find that, although a few exceptional countries exhibit zero‐waste compliance, most fare poorly, as exhibited by the high waste generation, incineration, and disposal (open dumping, landfilling) volumes. In the Global North, SWM strategies and practices rely heavily on technologies, economic tools, regulatory frameworks, education, and social engagement to raise stakeholder awareness and enhance inclusion and participation; in the Global South, however, many governments take sole legal responsibility for SWM, seeking to eliminate waste as a public “nuisance.” Separation and recycling in the Global South are implemented mainly by “informal” economies in which subsistence needs drive recyclable material retrieval. Imported, regionally inappropriate tools, economic constraints, weak policies and governance, waste trading, noninclusive stakeholder participation, data limitations, and limited public awareness continue to pose major waste and environmental management challenges across nations. In the context of the framework, we conclude that best practices from around the world can be used to guide decision‐making, globally. Despite variations in drivers and needs across regions, nations in both the Global North and South need to improve WH and CE compliance, and enhance stakeholder partnership, awareness, and participation throughout the SWM process. Partnerships between the Global North and South could better manage traded wastes, reduce adverse impacts, and enhance global environmental sustainability and equity, supporting UN Sustainable Development Goals. Integr Environ Assess Manag 2024;20:9–35. © 2023 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points Good and bad waste management practices exist in both the Global North and South. Waste trading and exported technologies cause impacts and risks in the Global South. Failures to comply with the concepts of waste hierarchy and circular economy result in high generation, incineration, landfill, and open dump rates. Better social awareness, inclusion, and participation improve practices, strategies, economic tools, and regulations.